IMPLIKASI HUKUM PERUSAHAAN DAERAH AIR MINUM TIRTA MUSI PALEMBANG MEMILIH PERUMDA ATAU PERSERODA SEBAGAI BENTUK BUMD - Silviani Margaretha; Joni Emirzon; Ridwan Ridwan (Fakultas Hukum Universitas Sriwijaya, 2024)
Government efforts that will hand over the management of water resources to State-Owned Enterprises (SOEs) / or through Regional Owned Enterprises (BUMD), must be followed by institutional and capital strengthening. While in this study, it will focus on PDAM Tirta Musi Palembang. In a legal perspective, in order to improve the quality of services, professional organizations, integrity and competitive organizations are needed so that with the issuance of Law No. 23 of 2014 on Regional Government above, opening opportunities to be reviewed and adjusted the status of regional companies' legal entities for the context of PDAM Tirta Musi Palembang City is expected to have an impact on improving the quality of services and professionalism of BUMD engaged in drinking water supply. In addition, through changes in the status of legal entities, it is hoped that the problems that have been faced by BUMD in general can be minimized such as weak efficiency, independence and supervision so that they can become competitive professional corporations. The research method used is normative research, namely literature research by examining library materials related to the problem being studied. To discuss the first problem in use Authority Theory, Legal Responsibility Theory, and Legal Entity Theory. The results of this study show that Perumda was considered more effectiveis for PDAM Tirta Musi Palembang because PDAM Tirta Musi Palembang is only owned by one ownership and engaged in business that concerns the lives of many people, namely in the management of drinking water and / or clean water for the people in the city of Palembang